2019
DOI: 10.1021/acsami.9b18425
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics-Controlled Dynamic Cell Niches Guided Osteogenic Differentiation of Stem Cells via Preserved Cellular Mechanical Memory

Abstract: Stem cells sense and respond to their local dynamic mechanical niches, which further regulate the cellular behaviors. While in naturally, instead of instantly responding to real-time mechanical changes of their surrounding niches, stem cells often present a delayed cellular response over a time scale, namely cellular mechanical memory, which may finally influence their lineage choice. Here, we aim to build a dynamic mechanical niche model with alginate-based hydrogel, therein the dynamic mechanical switching c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…Although type-1 collagen is known to induce osteogenesis even under basal conditions, 33 previous studies suggested that the key precipitator in stem cell differentiation for hydrogel-based 3D culture is the bulk matrix stiffness. 34,35 Osteogenesis was only observed when the complex modulus of hydrogels is above 37 kPa. In contrast, the IPN hydrogel cannot be too soft as previous studies have suggested that only hydrogels with a storage modulus of >1600 Pa supported mechanotransduced cell adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…Although type-1 collagen is known to induce osteogenesis even under basal conditions, 33 previous studies suggested that the key precipitator in stem cell differentiation for hydrogel-based 3D culture is the bulk matrix stiffness. 34,35 Osteogenesis was only observed when the complex modulus of hydrogels is above 37 kPa. In contrast, the IPN hydrogel cannot be too soft as previous studies have suggested that only hydrogels with a storage modulus of >1600 Pa supported mechanotransduced cell adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…This confounding parameter might interfere cell culture. Manipulation of miR-21 was proposed to erase this effect [28] but no references were available for execution under the circumstance of hMSCs osteogenesis. Second, the mechanical stimulus cultured hMSCs underwent depended on its posture.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, biomaterial stiffness can be dynamically manipulated via stimulation with a magnet, [ 24a ] temperature, [ 18 ] crosslinking density, [ 28 ] ion concentration, [ 30 ] and pH. [ 31 ] For example, Wei et al.…”
Section: Biophysical Cues Of Biomaterials For Regulating Stem Cell Behaviormentioning
confidence: 99%
“…created a dynamic hydrogel by immersing methacrylated alginate‐based hydrogel into CaCl 2 solution, in which the stiffness can be reversibly controlled via the introduction or removal of Ca 2+ from the hydrogel. [ 30 ]…”
Section: Biophysical Cues Of Biomaterials For Regulating Stem Cell Behaviormentioning
confidence: 99%